Building Leadership Capacity: Embracing of Inclusive and Culturally Responsive Practices to Promote Succession and Sustainability of Principals in Arctic Canada - Tomoloju, Olusoga Ayodele (Scholarship@Western, 2024)
This Dissertation-in-Practice (DiP) aims to explore organizational change frameworks to address the problem of practice in the Tundra Education System (TES, pseudonym), which has resulted in inconsistent implementation of inclusion and culturally relevant policies by principals. TES is situated in an Indigenous region of Arctic Canada and about eighty percent of principals are non-Indigenous people. To make a change process relevant to the context of TES, the Inuit Qaujimajatuqangit (IQ) principles, upon which education in TES is built, are integral components of the change implementation processes. Furthermore, the DiP addresses the questions â€œwhatâ€, â€œwhyâ€, and â€œhowâ€ of the intended change using both qualitative and quantitative methods of data collection. The leadership theories explored in leading the change are transformational and culturally responsive leadership; Critical theory, however, is the overarching theory that frames the change process because its tenets align with the leadership theories and promote social justice, equity, inclusion, and decolonization. For the desired outcomes to be achieved using a composite solution (e.g., implementation of a newly designed TES leadership framework with a mentorship program component), the DiP embraces Nadler Tushmanâ€™s congruence model for gap analysis, Deszca et al.â€™s change path model for leading the change , an integrated framework (e.g., Hirschâ€™s framework and Deszca et al.â€™s model) for the change implementation plan, Haiiloâ€™s framework for change communication plan, and Demingâ€™s PDSA model for monitoring and evaluation of the change process. It is envisaged that effective facilitation of the change process by the change agents, and active engagement of all participants, will lead to improved cultural competence, higher retention rate of principals, and knowledge mobilization across TES.